2018
DOI: 10.1542/hpeds.2017-0242
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver and Health Care Provider Perspectives on Cloud-Based Shared Care Plans for Children With Medical Complexity

Abstract: Although further studies are needed to understand the optimal design and implementation strategies, shared care plans that meet these specified requirements could mitigate perceived information barriers and improve care for CMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Some novel ideas that have been published include the feasibility of a cloud-based care plans for providers and families. Desai, et al found that providers were amenable to participating in these types of coordination [59] and this might be ideal for infants transitioning from several types of NICUs (community based, children's hospital, etc.) to a primary care provider.…”
Section: Discussionmentioning
confidence: 99%
“…Some novel ideas that have been published include the feasibility of a cloud-based care plans for providers and families. Desai, et al found that providers were amenable to participating in these types of coordination [59] and this might be ideal for infants transitioning from several types of NICUs (community based, children's hospital, etc.) to a primary care provider.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 High degrees of usability and personalization are important for sustained engagement with apps that track chronic disease. 39,40 Desai et al 41 recently described design requirements for cloud-based shared care plans for CMC. Despite differences in scope, our studies have several similarities, including the need for cloud-based accessibility, alerts, collaboration among multiple users, and tailoring to the specific user.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies exploring the use of LCPs by families and providers who care for CMC highlight several limitations in their implementation that diminish their accessibility, their trustworthiness to provide accurate information, and their utility as a care coordination tool. 8,[10][11][12] Existing LCPs are typically printed on paper or scanned into the electronic health record (EHR) by an individual provider or provider team, restricting editing capability of other providers within the or-ganization. 10,13 Some EHR-embedded LCPs may allow providers from a single organization to comanage care plan content; however, this excludes a multitude of providers who care for CMC outside of the organization from contributing or updating content.…”
Section: Background and Significancementioning
confidence: 99%
“…8,[10][11][12] Existing LCPs are typically printed on paper or scanned into the electronic health record (EHR) by an individual provider or provider team, restricting editing capability of other providers within the or-ganization. 10,13 Some EHR-embedded LCPs may allow providers from a single organization to comanage care plan content; however, this excludes a multitude of providers who care for CMC outside of the organization from contributing or updating content. 10,14 Most importantly, printed, scanned, or EHR-embedded LCPs do not allow caregivers, who are integral members of the care team, to comanage their child's health information even though they have the most updated information about the child's day-to-day care.…”
Section: Background and Significancementioning
confidence: 99%